293 Investigation on the prevalence of musculo-skeletal disorders among jute mill workers in india. (24th April 2018) - Gangopadhyay, Somnath; Das, Sayantika; Sinha, Shreya; Dasgupta, Santi Ranjan; Goswami, Subrata
Abstract : Introduction: Musculoskeletal disorders (MSDs) are reported maximum among jute mill workers of India. The present study is designed to find out the actual magnitude of the problems among jute mill workers and to identify the possible associations between discomforts and working postures of these workers. Methodology: This study was conducted among eight selected jute mills of India. 717 male jute mill workers actively engaged in work at least for one year were randomly selected in this study. Subjects with self-reported MSD complaints for at least last 12 weeks were included. A detailed posture analysis was performed among them by Ovako Working Posture Assessment System (OWAS) method. Results: Among all participants 55% had complained Chronic Low Back Pain (CLBP). Age had an important association with CLBP. Subjects in the age group of 40–59 years were more likely to have pain ( p =0.02). Regarding ergonomic risk factors, lifting of load of more than 20 kg ( p =0.04) and repetitive movements of limbs ( p =0.03) had significant associations with CLBP. Discussion: Present study identifies a significant prevalence of CLBP among jute mill workers. Regarding ergonomic risk factors, the study has identified that MSD is significantly associated with work related awkward postures, lifting of load above 20 kg, repetitive movements of limbs and prolonged standing during work. Jute mill workers are exposed to heavy workload with repetitive and forceful motions, which generally adopt awkward and uncomfortable postures and carrying of excessive loads that ultimately has got a great impact on their health. Therefore, this study suggests the urgent need for work place interventions for improvement of work related health of 3, 50, 000 Jute workers of India.